Social Transformation in Education: The Role of Teachers in Creating a Bully-Free School - Hakim, Latifa Dinar Rahmani; Baihaqi, Muhammad Abdilah (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores the dynamics of social transformation in educational settings by focusing on the role of teachers in fostering a bully-free school environment. The research seeks to identify the forms, causes, and handling strategies of bullying, as well as to understand the contributions of teachers in addressing such behaviors. Employing a qualitative descriptive approach with a case study design, data were collected through classroom observations and in-depth interviews with teachers and students. Data analysis involved reduction, display, and conclusion drawing, supported by methodological and source triangulation to ensure validity. The findings reveal that bullying behaviors in schools manifest in both verbal and physical forms, including name-calling, unauthorized borrowing of belongings, insults involving family members, hitting, and other forms of physical contact. These actions are often rooted in family-related factors and are reinforced by media exposure, particularly through television and mobile phone content. Teachers play a pivotal role in managing bullying by implementing direct intervention strategies, facilitating moments of reflection such as ritual ablution, and providing platforms for dialogue and resolution. In severe cases, professional counseling services within the school are activated to support affected students. This research highlights the significance of teacher responsiveness and culturally adapted conflict resolution in transforming school climates. Its novelty lies in examining how character education programs can be practically integrated with anti-bullying strategies in the classroom. The study recommends further exploration involving schools with diverse backgrounds across Indonesia to broaden the understanding of bullying prevention efforts. These insights contribute to the advancement of social sciences and humanities, particularly in educational reform and the promotion of safe learning environments.